2010
DOI: 10.1002/elan.200900627
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Voltammetry at a Mercury Electrode in the Presence of Nickel Ions

Abstract: At a mercury electrode, Hcy and Cys yield similar cathodic stripping peaks connected to the reduction of the pertinent mercury thiolate. However, due the different behavior as a ligand for nickel ion, the above compounds perform very differently in the presence of this ion. Whereas the nickel ion at a high enough concentration suppresses the Cys peak, in the case of Hcy it causes the cathodic peak to shift to more negative potentials. The peculiar behavior of Hcy is due to the stabilization of the mercury thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It was indicated that active complexes are formed on the electrode's surface, which mediates electron transfer. It should also be noted that due to the mentioned electrochemical reactivity of both homocysteine and homocystine, which react with mercury in the same way as cysteine and cystine [39], we can discuss Bi -Hg2(SR)2 or Bi -Hg(SR)2 complexes. According to the literature reports [31], Bi(III) reacts with mercury cysteine thiolate -Hg(SR)2.…”
Section: Effects Of Protonation Of Some Amino Acids On the Kinetics Amentioning
confidence: 99%
See 1 more Smart Citation
“…It was indicated that active complexes are formed on the electrode's surface, which mediates electron transfer. It should also be noted that due to the mentioned electrochemical reactivity of both homocysteine and homocystine, which react with mercury in the same way as cysteine and cystine [39], we can discuss Bi -Hg2(SR)2 or Bi -Hg(SR)2 complexes. According to the literature reports [31], Bi(III) reacts with mercury cysteine thiolate -Hg(SR)2.…”
Section: Effects Of Protonation Of Some Amino Acids On the Kinetics Amentioning
confidence: 99%
“…This form of anodic mercury oxidation in the presence of homocysteine or homocystine is adsorbed in the range of Bi(III) reduction potentials (~ 0 mV) and is loosely bonded to the electrode's surface [34,35]. However, in the case of polarographically non-active ethionine, complexes of type Bi -ethionine are formed on the electrode's surface [39,40].…”
Section: Effects Of Protonation Of Some Amino Acids On the Kinetics Amentioning
confidence: 99%